Strategies for creating undergraduate research and outreach experiences - Fadie T. Coleman; Danielle E. Graham (BMC Proceedings, 2025)
Abstract Engaging students in research and outreach offers a range of benefits, including acquiring scientific knowledge and critical skills, fostering science identity development and increasing persistence in science, and providing broad exposure to STEM careers. Although undergraduate research experiences have been shown to be impactful for developing scientists, exploring ways in which all students can experience these opportunities is an important focus that merits continued discussion. This paper will discuss ways in which well-known strategies for incorporating research into science curricula can be further adapted to have a broader impact on undergraduate education and science outreach programming. In addition, key insights inspired by an “Adapting Your Research for Teaching and Outreach” workshop will be considered. Lastly, this paper will discuss ways in which inclusive strategies can facilitate practical application across diverse educational settings.